Can anyone be objective about Donald Trump? Assessing the personality of political figures. Issue 3 (3rd July 2021) - Nai, Alessandro; Maier, Jürgen
ABSTRACT: Are expert observers and the public at large able to provide an objective assessment of the personality of political figures? We provide special attention to the (curious) personality of Donald Trump and triangulate data from seven sources: two mass surveys with US citizens, three expert surveys (in the USA, Germany, and the Netherlands), and two surveys with undergraduate students in the Netherlands. This triangulation allows us to highlight that in the US public opinions about Trump are extremely polarized even beyond partisanship; for instance, agreeable voters tend to have a better opinion of Trump if they are Democrats, whereas disagreeable individuals tend to have a better opinion of Trump if they are Republicans. Experts, on the other hand, are not as dramatically driven by their ideological preferences as some might fear, and they globally seem to agree on his extreme profile. Non-experts (Dutch students) are equally able to draw a consistent profile of Trump, more or less regardless of their personal preferences, as are experts – something that US voters seem incapable of, especially if leaning towards the right. Finally, experts and students also assess consistently the personality of selected other political figures beyond Trump – Angela Merkel, and two leading figures in Dutch politics.